2000
DOI: 10.1037/0893-3200.14.3.510
|View full text |Cite
|
Sign up to set email alerts
|

Black and White girls' racial preferences in media and peer choices and the role of socialization for Black girls.

Abstract: This exploratory research compared Black and White girls' racial preferences as exhibited through their media (music and television) and peer choices. The sample included 140 8- and 9-year-old Black and White girls of various socioeconomic levels. Findings suggested that both Black and White girls have more Black music preferences than White or no-race music preferences. Also, both Black and White girls made more White television program choices than Black or no-race choices. In their peer selections, all girl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
23
0

Year Published

2006
2006
2015
2015

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(25 citation statements)
references
References 46 publications
2
23
0
Order By: Relevance
“…Instead, they may compare themselves to other Black women within their own community-the members of their family, the friends they know, and more importantly, the Black female characters in the media. In fact, previous studies have suggested that African American people consistently showed their preferences for black-oriented media, and that they also rated the programs featuring Black characters as their most favorite programs (Allen 2001;Elliott 2003;O'Connor et al 2000). Therefore, it is likely that Black female models depicted in the media may have the most effect on African American women's body image conceptions.…”
Section: Theories and Black Females' Body Imagesmentioning
confidence: 85%
“…Instead, they may compare themselves to other Black women within their own community-the members of their family, the friends they know, and more importantly, the Black female characters in the media. In fact, previous studies have suggested that African American people consistently showed their preferences for black-oriented media, and that they also rated the programs featuring Black characters as their most favorite programs (Allen 2001;Elliott 2003;O'Connor et al 2000). Therefore, it is likely that Black female models depicted in the media may have the most effect on African American women's body image conceptions.…”
Section: Theories and Black Females' Body Imagesmentioning
confidence: 85%
“…For instance, adolescents who believe more strongly in the importance of teaching about racism are more likely than their counterparts to evidence more advanced stages of ethnic-racial identity development (Stevenson, 1995). African American adolescent girls whose mothers engage in greater preparation for bias are more likely to have Black over mixed-race or White music preferences (O'Connor et al, 2000). In the NSBA, however, there were no significant differences in ethnic identity among adults who received messages about discrimination, those who received messages about egalitarianism, and those who received no ethnic-racial socialization messages (Demo & Hughes, 1990).…”
Section: Ethnic Identitymentioning
confidence: 99%
“…Within the various models of racial and ethnic socialization, scholars have identified two fundamental types of messages central to ethnic minority families: (a) messages that transmit cultural pride, history, heritage, traditions, and customs (Hughes et al, 2006; O’Connor, Brooks-Gunn, & Graber, 2000), and (b) messages that prepare children for the challenges of explicit and implicit discrimination and consequent health, social, and economic disparities. Messages relevant to transmission of culture have largely been described by constructs such as cultural socialization (Hughes & Chen, 1997), pluralism, reinforcement of cultural pride, appreciation of cultural legacy (Stevenson et al, 2002), and integrative/assertive socialization (Demo & Hughes, 1990).…”
Section: Interpersonal Cultural Risk and Resilience Factorsmentioning
confidence: 99%